The Impact of COVID-19 Pandemic on Sexually Transmitted Infections - Rita Bouceiro-Mendes; J. Borges- (Sociedade Portuguesa de Dermatologia e Venereologia, 2021)
Novel coronavirus disease of 2019 (COVID-19) has impacted health care in general and has disrupted our routines. Health care services were mostly directed towards the emergency response and containment measures to halt virus spreading have been applied worldwide. It has also indirectly impacted the transmission of other infections, including sexually transmitted infections (STI). For STI, physical distancing measures have the potential to decrease STI transmission whereas the impact of COVID-19 on healthcare resources with interruption of STI diagnosis and treatment drives in the opposite direction. The question is how the counterbalancing impact of these forces will affect the course of STI epidemic. In this article we review the current available data on the COVID-19 impact on sexual behaviours, STI services interruption and reported STI rates, including local data.